Henry Cisnersos visiting Villa Nueva
Photograph shows Henry Cisneros speaking at the YWCA's Villa Nueva. He is standing at a podium and speaking into a microphone. There is a sign on the podium that reads: "YWCA in Santa Clara Valley." A women is seated in a chair to the right of the podium.